HbE dan diabetis melitus lapuran akhir projek jangka - Mazlan, Musalmah; Jamaludin, Normah; Bebakar, Wan Mohamad Wan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2003)
Glycated hemoglobins (HbAiiHbAic) serves as an indicator of diabetic control and hence the effectiveness of treatment. Studies on the methods available have shown that factors such as hemoglobin concentration and the presence of high lipid in the blood may affect the validity of the results. Atypical hemoglobins such as HbS and HbC have also been shown to affect the determination of glycated hemoglobins. However no study has been done on the effect of HbE , the hemoglobin variant that is present in the South East Asian population. Thus this study was unde~ to determine the effect of HbE on fu~ - determination ofHbAI/HbAlc by 4 commercial kits and also to determine its prevalence among diabetic subjects in Kelantan. Blood was taken from 58 normal subjects (23 males and 35 females) and 63 HbE (31 males and 32 females) heterozygous subjects. All subjects ,bad no history of diabetes mellitus. They had random blood glucose values < 7.8 mmolll and hemoglobin (hb) values between 7 to 24 g/dl. The EDTA plasma collected were tested for HbAI and HbAlc using 4 commercial kits i.e. Eagles Diagnostics, Boehringer Mannheim (BM), Diastat and Ames DCA 2000. The tests were done within one week and samples were stored at 4 oc before analysis. Results showed that the mean± s.d HbAI levels in normal vs HbE heterozygous subjects using Eagles Diagnostics, Boehringer Mannheim and Diastat kits were 6.9 ± 1.1% vs 9.5± 3.9%; 7.1 ± 1.2% vs 14.8 ± 9.3% and 8.3 ± 3.8% vs 13.5 ± 10.8% respectively. All were significantly different (p<O.OOI). The mean± s.d HbAlc levels for normal vs HbE heterozygous subjects determined using Ames DCA 2000 and Diastat kits were 5.1 ± 0.5% vs 5.3 ± 2.7% and 6.1 ±.).9% vs 10.7 ± 8.7% respectively. The results measured using the Diastat kit were significantly different (p<0.001) while those measured using the Ames DCA 2000 kit were not significantly different (p = 0.5). Therefore the cation-exchange chromatography based kits (Eagles Diagnostic, 7 . Boehringer Mannheim and Diastat) were affected by the presence of HbE. This - interference was minimised by dilution. The use of~pecific antibody (Ames) did not have any influence on HbA 1 c determination. The prevalence of HbE among diabetics were also studied. Blood was taken from 202 diabetic patients (121 females and 81 males; aged 46.2 ± 15.2 years) who were attending the outpatient diabetes clinic, Hospital USM. 28 patients (13.9%) were confirmed to carry HbE by hemoglobin electrophoresis. This consists of 4 males and 24 females. The finding is consistent with the prevalence ofHbE heterozygotes in the general population. In conclusio~ this study showed that HbE affect the determination ofHbAl/HbAlc by kits using cation exchange chromatography and that the interference may be diluted out The prevalence of HbE among diabetes mellitus patients is similar to that of the general population.